INTERTEXTUAL ANALYSIS OF “SANG ALKEMIS” BY PAULO COELHO AND “SANG PEMIMPI” BY ANDREA HIRATA - Irma Satriani (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This study aims to reveal the intertextuality in Sang Alchemist by Paulo Coelho and Sang Pemimpi by Andrea Hirata. Narrative structure analysis is related to intertextuality and describes the novel Sang Pemimpi as a transformation from the novel Sang Alchemist by Paulo Coelho as its hypnogram. Using descriptive qualitative methods and theoretical concepts related to narrative structure and transformation, this study concludes that Sang Alchemist is a program of Sang Pemimpi regarding plot, characters, and themes. In the plot appears the intertextual that can be seen at the story's beginning, trying to pursue dreams, parents' attitudes, despair, and the completion stage.